INTEGRATION OF ERASMUS+ STUDENTS IN ENTREPRENEURSHIP CLASSES - Almeida, Fernando (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Exchange students programs in higher education under the Erasmus+ initiative play a fundamental role in providing an international experience for students while they are studying. In the framework of Erasmus+ students show interest in having a new experience, different from what can be offered in their institution of origin, namely by acquiring new technical, social and behavioral skills. Due to its scope and structure, the entrepreneurship course offers the conditions of attractiveness and integration of these students, enabling them to formulate a new business in multicultural and multi-disciplinary teams. This study, through the use of a qualitative methodology based on a focus group and in-depth interviews, reports the experience faced by Erasmus+ students in the frequency of an entrepreneurship course. Four research questions were explored, namely the main challenges felt by these international students, perceived benefits, the impact of their formation and the collaboration given by these students in the working groups. The results obtained allowed us to identify a set of difficulties of integration, but it was also possible to recognize that the skills that were acquired and the heterogeneity of their formation contributed positively for success of the entrepreneurship projects.